Enhancing student skills through culinary competitions: Developing grounded theory from the bachelor of home economics program - Layim, Tanavit; Prachongpun, Papimon; Kayadee, Nichapavee; Aemprom, Sureerat (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aims to evaluate the proficiency of undergraduate students in a Home Economics curriculum. The study analyzed a group of 17 students majoring in food nutrition and 4 students majoring in food business who participated in a cooking competition. Data were examined from 2022 to 2024, which employed semi-structured, in-depth interviews. Data analysis employed triangulation. The results showed that students could classify their innate skills into four distinct groups. Self-development refers to students' active pursuit of personal improvement, aimed at enhancing their capacity-building. Self-efficacy has increased their potential to identify and acknowledge their proficiencies across many domains of expertise. They demonstrated self-awareness by thoroughly understanding their capabilities, acknowledging their societal viewpoints, and maintaining a heightened level of self-awareness even when faced with challenges. Self-esteem is defined as an individual's ability to acquire understanding and abilities by cultivating confidence. Educational procedures described here promote the acquisition of knowledge. The brain's physiological systems control intricate neural processes that underpin brain-based learning. It is responsible for the cognitive processing of the five senses. The cognitive growth and maturity of pupils greatly relied on the cultivation of abilities and understanding of knowledge through intellectual processes. The influence of the body on the mind affects students' desires to achieve positive outcomes, which enhances their mental processes.